PENGGUNAAN METODE MEMPERBAIKI PELAFALAN UNTUK MENINGKATKAN KEMAMPUAN 4 NADA BAHASA MANDARIN SMP KEMALA BHAYANGKARI - Joti Joti; Lily Thamrin; Lusi Lusi (Universitas Tanjungpura, 2019)
AbstractTone plays an important role in Chinese teaching. Different tones represent different meanings. In Chinese teaching, orthodontics can help students master the tone of Chinese. The purpose of this study is to understand how to use orthodontic method to teach Chinese four tones and whether orthodontic method can improve students' ability to master Chinese four tones. The subjects were students of Class 1, Grade 1 of KEMALA BHAYANGKARI Junior Middle School. There were 24 students (13 boys and 11 girls).In order to understand the mastery of Chinese four tones by KEMALA BHAYANGKARI junior middle school students, the research methods used by the author are experimental method and test method. According to the teaching experiment and the statistics and analysis of the pre-test and post-test, the author understands that the orthodontic teaching method can effectively improve the students' ability to master the four tones of Chinese.Key words: tone, four tones,orthodontic pronunciation